ECONOMIC DEVELOPMENT PARADIGM IN IBNU KHALDUN'S ECONOMIC MODEL: SYSTEMATIC LITERATUR REVIEW - Zulfikar, Zulfikar; Nawawi, Zuhrinal M.; Harahap, Isnaini (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
: The economic development paradigm in Ibn Khaldun's economic development model is based on the interdependence of economic and political variables. The model emphasizes the importance of justice and development in maintaining the stability and prosperity of a country. The aim of this systematic literature review (SLR) is to analyze how Ibn Khaldun's economic development model relates to the Preferred Reporting Items for the Systematic Review method. Data was obtained from online databases, namely Crossref, Google Scholar, Semantic Scholar, and Scopus (2018-2023), and 19 articles were obtained that were relevant to the research. By using the keyword search "Ibn Khaldun's economic development model" the model developed in this research provides a better understanding of the interdependence of economic and political variables and can be used as a basis for developing development models in the context of his theory. The article concludes that Ibn Khaldun's economic thinking in the circle of equity theory shows the existence of a dynamic relationship and interdependence between these variables, where the government cannot be implemented without the implementation of sharia, as well as the quantity and quality of human resources, especially those working productively will be able to improve the economy and development of a country